Holistic approach on bioactivities, phytochemicals, nanoparticle biosynthesis and endophyte isolation from two Ficus species - Nushiba Naser P. T (Department of Botany, University of Calicut, 2024)
Ficus plants are known for their therapeutic benefits and symbolic significance in religion and culture. They have played a significant role in ancient indigenous medical methods, such as Ayurveda, Siddha, Unani, and Homoeopathy. The fruit of various Ficus plants, particularly the fig Ficus carica, is rich in antioxidants and health-benefitting polyphenols. Members of this genus contribute to various medicines in ayurveda, such as "Pancha Valkala Kashaya". However, most research focuses on a small number of plants, so there are a number of Ficus species that are overlooked. Ficus drupacea Thunb. and Ficus exasperata Vahl, comes under this type of plants. The present study encompasses two different phases and each phase contain various parts. The first phase contains major three parts such as phytochemical profiling, bioactivity studies and silver nano particle’s formulation. The second phase contain three parts in which isolation and identification of the fruit fungal endophytes from the two species is the first part, biochemical analysis of the fruit fungal endophytes comes as the second part and nanoparticle biosynthesis and associated studies is the third part. Phytochemical assays were conducted as two part using preliminary studies with three solvents based on their polarity viz hexane, methanol and water. Polar solvents were good at eluting various phytochemical groups and so among the polar solvents water was selected due to its nontoxic nature towards biological system. Phytochemical delineation of the four aqueous extracts such as leaf and fruit of F. drupacea and F. exasperata revealed ninety-two non-volatile and ten volatile compounds, which falls under the major phytochemical groups, alkaloids, phenols, terpenoids, glycosides etc. Major two activities such as antioxidant and anticancer activities were studied using the extracts. In the antioxidant study four important in vitro antioxidant assays such as DPPH radical scavenging assay, hydroxyl radical scavenging assay, nitric oxide scavenging assay and superoxide radical scavenging assays were conducted. Even though concentration dependent variation, ie., (an increasing percentage inhibition with increasing extract concentration) was reported, over all ability to scavenge free radicals seems to be moderate with the four-extracts used in the study. Anticancer activity was also tested using the four aqueous extracts on MCF-7 breast cancer cell lines. Toxicity studies were also conducted on the normalcell line L929 to assess the ability of the extract to distinguish and save the normal cells while harming only the cancer cells. Anticancer assay revealed potential anticancer activity with the four extracts. Among the four extracts, F. drupacea fruit extract was found to be very effective with its anticancer ability specifically to target the cancer cells and giving least cytotoxic effects on the normal cell lines. This extract was chosen for further studies. Apoptosis detection was done using double stain method as well as comet assay. The study revealed that the cause of antiproliferative action was due to apoptosis but not necrosis. Studies continued to analyze the ability of the fruit extract in causing cell cycle arrest and gene modulation. Cell cycle arrest was reported with the G1 phase which was supported by the cell cycle regulation assay by flow cytometry. The gene expression studies on both p53 and STAT 3 further confirmed the anticancer activity of the cells with increased expression of P53 and down regulation of STAT 3 which were the basis of apoptosis and cell cycle arrest. The third part of the first phase was bio fabrication of nanoparticle from the four aqueous extracts (leaf and fruit extracts of F. exasperata and F. drupacea). Silver nanoparticles were readily synthesized from the four-extract considered in the current study. Visual indication of colour change was further confirmed by the UV-vis spectroscopy as well as SEM imaging. The nanoparticles biosynthesized were able to produce a constitutive peak for silver in the UV- vis range and nearly spherical shaped nanoparticles that falls under the size range of 20-50 nm were produced. When these nanoparticles were tested for their antimicrobial efficacy, they seem to be better antimicrobial agents in the higher concentration and they could produce zone of inhibition nearly comparable to the positive control used in the study. In phase two the study revealed the presence of fungal endophytes from the two plants both from fruits and leaves. 11 fungal endophytes were isolated from the leaves and fruits. Fruits were reported to have a single endophyte which is similar for both F. exasperata as well as F. drupacea. All the 10 fungal endophytes from the leaves of both plants were identified to the species level using the BLAST analysis based on ITS and LSU region. All the fungal isolates were from the division Basidiomycota and Ascomycota. Fruit fungal endophyte of F. drupacea was subjected to phytochemical profiling and 34 compounds were reported. This fungal extract was used in the synthesis of gold and silver nanoparticles. These nanoparticles were found to have anti-microbial action against two gram negative bacteria E. coli and Salmonella paratyphi.
Keywords: FIcus; Breast cancer; MCF 7; Nanoparticle; Endophytes